Utility of bone SPECT/CT to identify the primary cause of pain in elderly patients with degenerative lumbar spine disease - Satoshi Kato; Satoru Demura; Hidenori Matsubara; Anri Inaki; Kazuya Shinmura; Noriaki Yokogawa; Hideki Murakami; Seigo Kinuya; Hiroyuki Tsuchiya (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background Diagnosis of the cause of low back pain in the presence of degenerative spine disease using conventional imaging techniques, especially in elderly individuals, is challenging. Our aim was to describe our use of bone scintigraphy with single photon emission computed tomography (bone SPECT/CT) in the assessment of low back pain in elderly patients with degenerative lumbar spine disease, underlining the clinical utility of bone SPECT/CT imaging in this clinical population to inform diagnosis and treatment. Methods Between January 2016 and December 2017, we used bone SPECT/CT to successfully identify the cause of low back pain in five elderly patients. All patients had been scheduled for extensive spinal fusion surgery based on conventional imaging (plain radiography, computed tomography, and magnetic resonance). Results After diagnosis using bone SPECT/CT, three patients underwent spinal fusion at 1–2 levels with specific degenerative disk and joint disease, with the other two patients successfully treated using a conservative approach for a non-traumatic insufficiency fracture of the endplate of the L4 vertebral body and a fracture of the transverse process of L3. Clinically meaningful decrease in pain and fracture healing were obtained with conservative treatment. Conclusion Bone SPECT/CT was useful to identify the specific cause of pain in elderly patients with lumbar degenerative disease and to provide appropriate treatment, avoiding the unnecessary use of invasive spinal fusion surgery. Therefore, the clinical utility of bone SPECT/CT is potentially high as it improves diagnosis and lowers the risk of inappropriate invasive spinal surgery.